Նորակազմությունները Սահակ Ձորոփորեցու երկերում - Գրիգորյան, Սուսաննա; Պարոնյան, Նաիրա (ԳԱԱ ԼԻ հրատ․)
Саак Дзоропореци развивал широкую летописную деятельность. Он сочинял тирады, богословские труды. Его сочинения представляют особый интерес в языковом значении. Эти сочинения отличаются своими теологическими, художественными достоинствами. Представляемая статья посвящена изучению более 70 слов, которые не имеются в больших толковых словарях древнеармянского языка. Автор мастерски использовал весь богатый лексический состав нашего языка, а также, по мере необходимости, словообразовательные возможности армянского языка, создавая новые слова, обогащая тем самым язык собственныõ произведений и состав литературного языка. Очень немногочисленны префиксально – суффиксальные неологизмы, которые в основном, благозвучны и образованы соответственно законам и законамерностям словообразовательной традиции армянского языка. Sahak Dzoroporetsi had a great role in the literary history of the Armenian church. He wrote tirades and theological works. Sahak Dzoroporetsi’s works are of special interest from the linguistic point of view. These works are unique in their theological, literary merits. The present article is devoted to the study of more than 70 words, which are not present in the voluminous dictionaries of Old Armenian. The author masterly used the whole rich vocabulary of our language, he also made use of the opportunities of Armenian word-formation, creating new words and word-combinations and did it in such a way that he could enrich not only the language of his works, but also our literary language. There are few prefixal - suffixal neologisms which are in general euphonious and are formed according to the rules and regularities of the tradition of the Armenian word-formation.
Keywords: Բառակազմություն